First study of cloud to ground lightning discharges using ground-based observations over Indian subcontinent and its possible relationship with carbon dioxide and aerosols. (July 2022) - Dube, Adarsh; Maurya, Ajeet Kumar; Dharmaraj, T.; Singh, Rajesh
Abstract: We report the first estimation of Cloud to Ground (CG) lightning activity over the Indian subcontinent. Initial results from the analysis of ground-based data of worldwide lightning location network (WWLLN) over the Indian region are discussed. The CG lightning density is analysed from the quality controlled WWLLN data for three years during 2009–2011. The lightning flash density (LFD) analysis is shown with high and low LFD regions spatially. The LFD is enhanced by 20% in year 2010 and 13% in year 2011 in comparison to LFD in the year 2009 over the eastern sector. Over the west coast (around geo latitude 20 0  E) there is a 30% increase in LFD in 2010 and 17% increase in 2011. Over the Bay of Bengal, there is an increase of up to 66% LFD at few places in both the years. Aerosols and carbon dioxide (CO2 ) being the two most significant species in the Earth atmosphere responsible for atmospheric heating and convection are studied for the variations in their concentration during this period. There is an enhancement of 4 ppm in the CO2 concentration over the study region in 2010 and 7 ppm in 2011 corresponding to enhancement in LFD. The Aerosols concentration over Indian mainland has increased up to 50%. Over the Arabian Sea and Bay of Bengal the aerosol optical depth (AOD) is found to decrease 25% where lightning flash density is found to reduce from the previous year. We find positive correlation between LFD-aerosols and LFD-CO2 . Overall, there is an increasing trend of atmospheric temperature, LFD, aerosols and CO2 . The cloud microphysical effect that may have been impacted due to increase in air temperature, AOD and in concentrations of CO2 in the atmosphere is investigated with this study of lightning discharges. Highlights: Lightning activity over the Indian subcontinent reported for the first time using observations from a ground based dataset. Possible role of surface atmospheric pollutants such as CO2 and aerosols in increasing atmospheric heatingand convection. Crucial role of aerosols for convection and thunderstorms/lightning discharges in the atmosphere. Positive correlation between LFD-aerosols and LFD-CO2 .